EXAMINING THE INTERSECTION OF SPORTS EVENT MANAGEMENT AND CORPORATE SPONSORSHIPS - Gaikwad, Sunita Popat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The intersection of sports event management and corporate sponsorships plays a crucial role in the modern sports business landscape. Corporate sponsorship has evolved beyond mere financial support, now representing a strategic tool for brand exposure, audience engagement, event profitability and long-term market positioning. This paper investigates the evolving dynamics between sports event managers and corporate sponsors, analysing their collaboration to enhance event experiences, maximize profitability, and solidify sponsor-brand relationships. Key focus areas include sponsorship activation, audience targeting, brand alignment, economic impact on both parties and the logistical management of sponsorships. The paper further explores successful case studies of major events such as the Olympics, FIFA World Cup, and the Super Bowl, emphasizing the methods used by event organizers to leverage sponsorships to meet business objectives. Through case studies and statistical analysis, the paper underscores the evolving role of sponsorships in sports event management and provides a framework for maximizing the potential of these corporate partnerships.